Evaluation of rheo-viscoelasticity of magnesium-silicate-hydrate mixes incorporating different superplasticizers - Yiming Peng; Cise Unluer (Developments in the Built Environment, 2024)
This study investigated rheo-viscoelastic behaviors of MgO-SiO2 pastes with three phosphate additives (sodium hexametaphosphate (SHMP), sodium trimetaphosphate (STMP), and sodium orthophosphate (SOP)) as superplasticizers. Static yield stress, dynamic yield stress, median differential viscosity, thixotropic loop area, structural recovery rate, and non-destructive structural build-up were analyzed. Furthermore, assessment of hydration and particle dispersion stability was facilitated by employing isothermal calorimetry, XRD, DTG, and zeta potential techniques. SHMP significantly decreased the static and dynamic rheology, thixotropy, and viscoelastic evolution. Samples incorporating 2 wt% SOP exhibited enhanced rheological parameters, particularly static yield stress, owing to increased brucite formation and a denser microstructure in the fresh paste. Adsorption of phosphate additives on MgO surfaces inhibited formation of brucite and improved interparticle electrostatic repulsion, thereby increasing suspension stability. High-efficiency adsorption of SHMP on MgO surfaces, coupled with the retardation of brucite nucleation-and-growth, and enhancement in suspension stability, greatly restrained the rheo-viscoelastic evolution of MgO-SiO2 system.